The Reality of the World and the Multidimensionality of the Reality of the Individual: The Semantic Meaning of Architecture of Consciousness - Kalishchuk, Svitlana M. (Journal of Intellectual Disability - Diagnosis and Treatment, 2020)
In psychology, the world’s multidimensionality is manifested in the study of consciousness, in identifying the methodological foundations of psychology and psychology of consciousness. The structure of the multidimensional world of a man is described from the point of view of the subject’s understanding of the characteristic features of the realities where man lives. Aims of study are to formulate and consider the problem of the world’s reality and the multidimensionality of the reality of the individual in the perspective of the semantic architecture of consciousness and within the framework of a holistic model of representation of the psychology of understanding the human world. The pragmatic aim of the present research is to set a quantitative measure in which a person is drawn into virtual reality (TER). The meta-analysis of publications with quantitative empirical data reporting on the results of staff training using virtual and augmented reality. The criteria of the search were that articles must be published exceptionally in peer-reviewed journals and be issued not older than in 2017. The platform for the effective search was the Google Scholar search engine. The transfer efficiency factor (TER) was the key element of the analysis. All gathered data extracted from the relevant literature sources were interpreted through observation, description, quantitative calculation, complex analysis, methods of comparison, generalization, and abstraction method. Although learning conditions with more virtual immersion lead to slightly worse results than real learning conditions, most people show similar results after learning, regardless of the level of virtual immersion. The inhomogeneity of acceptance by individuals of virtual reality is found out in quantitative data of the considered studies. The average score for the performance of each training condition represented in the scientific works considered for this study, as well as the 95% confidence interval, was calculated. It was found out that the value of TER 0.5 turned into a percentage by multiplication by 100%, indicates that training on the simulator can reduce the time of personal training by half. Presence is a psychological phenomenon that occurs in the human mind, not in specific technologies. The usage of virtual reality in learning affects the sense of presence and immersion. It directly affects an individual’s perception of world reality. At the same time, the individual consciously accepts the picture of simulated reality, which emphasizes the multidimensionality of the individual’s reality.